The biological denitrification coupled with chemical reduction for groundwater nitrate remediation via using SCCMs as carbon source. (November 2019) - Zhang, Wen; Bai, Ying; Ruan, Xiaohong; Yin, Lin
Abstract: Renewable additional carbon sources for groundwater denitrification, such as sustainable-releasing compound carbon source materials (SCCMs), are required. This work reports long-term groundwater denitrification with permeable reactive barriers filled with SCCMs; the coupling of biological denitrification and chemical reduction avoided the need for a continuous carbon source supply. Four 370-day lab-scale permeable reactive barrier experiments with four SCCMs showed that NO3 − removal efficiency in zero-valent iron (ZVI) SCCMs was higher than in ZVI-free SCCMs. In the ZVI SCCMs, the NO3 − removal reaction began quickly in the early stage, owing to ZVI chemical reduction, whereas biological denitrification was lower and incomplete with a NO2 − concentration of 0.8 mg L −1 in the ZVI SCCM system. As the chemical reduction efficiency decreased, the biological denitrification efficiency increased, and the highest NO3 − removal efficiency was 98.8%. Decreasing the Fe 2+ concentration decreased ZVI chemical reduction. High-throughput sequencing indicated that the proportion of denitrifying bacteria attached to the SCCMs was up to 34.4% at the family level, leading to the denitrification gene being predominant. Quantitative PCR indicated increased microbial metabolic activity, richer bacterial community diversity, and more bacteria. Long-term monitoring data for SCCMs will help realize the use of biological denitrification coupled with chemical reduction for groundwater NO3 − remediation. Highlights: SCCMs used for groundwater remediation are acted as renewable carbon sources. The functional denitrification microbial community attached on SCCM was satisfied. The long-term biological coupled with chemistry denitrification was realized. Bacterial community diversity was enhanced by proper and sustained carbon supply. The feasibility of PRB used SCCMs was suggested for high NO3 − –N removal efficiency.